2012
DOI: 10.3233/jae-2012-1583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electromigration on diffusional creep in polycrystalline materials

Abstract: An analysis was made of the diffusional creep in polycrystalline materials when subjected to simultaneous action of tensile stress and electric current. Incorporating the contribution of electromigration to atomic diffusion in grain boundaries, the problem of grain boundary diffusion was solved. A simple relationship was derived between diffusional creep rate and local electric field intensity (current density). The results showed that electromigration can enhance the diffusional creep in polycrystalline mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Liu H. Y. et al [10] reported stress-relaxation rate of tin-based solder joint increased significantly after current stressing. Pharr M. et al [11] and Shao, S. S. et al [12] analyzed and discussed the effect of EMinduced diffusion on creep behavior based on theoretical calculation. These literatures demonstrated that when analyzing creep of a real solder joint, EM must be taken into account because of the interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…Liu H. Y. et al [10] reported stress-relaxation rate of tin-based solder joint increased significantly after current stressing. Pharr M. et al [11] and Shao, S. S. et al [12] analyzed and discussed the effect of EMinduced diffusion on creep behavior based on theoretical calculation. These literatures demonstrated that when analyzing creep of a real solder joint, EM must be taken into account because of the interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) The intensification of the current field assisted sliding rate and diffusional creep [14][15][16] Such metals and their alloys as copper, nickel, aluminum, tin, etc. [1][2][3]6] show the increase in their steady-state creep due to the passage of direct current (DC).…”
Section: Introductionmentioning
confidence: 99%